Substance use referral, treatment utilization, and patient costs associated with problematic substance use in people living with HIV in Cape Town, South Africa. - Belus, Jennifer M; Regenauer, Kristen S; Hutman, Elizabeth; Rose, Alexandra L; Burnhams, Warren; Andersen, Lena S; Myers, Bronwyn; Joska, John A; Magidson, Jessica F (2022)
INTRODUCTION: Despite efforts to detect and treat problematic substance use (SU) among people living with HIV (PLWH) in South Africa, integration of HIV and SU services is limited. We sought to understand whether PLWH and problematic SU were: (a) routinely referred to SU treatment, a co-located Matrix clinic, (b) used SU treatment services when referred, and (c) the individual amount spent on SU. METHODS: Guided by the RE-AIM implementation science framework, we examined patient-level quantitative screening and baseline data from a pilot clinical trial for medication adherence and problematic SU. Qualitative data came from semi-structured interviews with HIV care providers (N = 8), supplemented by patient interviews (N = 15). RESULTS: None of the screened patient participants (N = 121) who were seeking HIV care and had problematic SU were engaged in SU treatment, despite the freely available co-located SU treatment program. Only 1.5% of the enrolled patient study sample (N = 66) reported lifetime referral to SU treatment. On average, patients with untreated SU spent 33.3% (SD=34.5%) of their monthly household income on substances. HIV care providers reported a lack of clarity about the SU referral process and a lack of direct communication with patients about patients' needs or interest in receiving an SU referral. DISCUSSION: SU treatment referrals and uptake were rare among PLWH reporting problematic SU, despite the high proportion of individual resources allocated to substances and the co-located Matrix site. A standardized referral policy between the HIV and Matrix sites may improve communication and uptake of SU referrals.